2016
DOI: 10.1111/1753-6405.12402
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of diagnosis, care and treatment among Aboriginal people living with hepatitis C

Abstract: Objective: Aboriginal Australians are disproportionately affected by hepatitis C (HCV). There are a range of barriers to HCV care, often beginning with poor diagnosis experiences. Little research exists on the experiences of Aboriginal Australians living with HCV. This study aimed to describe their patterns of HCV care and treatment with specific emphasis on the impact of their being informed of their diagnosis in a culturally sensitive manner. Methods:A total of 203 Aboriginal people living with HCV were recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…However, in a setting with public coverage of DAAs for eligible patients as ours, other factors may better explain differences in treatment access between white and non‐white participants. Among these, a growing body of evidence has highlighted how the dual stigma that PWID of Indigenous ancestry face when trying to access healthcare can result in delaying or forgoing needed care altogether . Collectively, these findings underscore the need for safe and culturally‐appropriate health services to optimize engagement in HCV care and improve health outcomes among Indigenous people.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a setting with public coverage of DAAs for eligible patients as ours, other factors may better explain differences in treatment access between white and non‐white participants. Among these, a growing body of evidence has highlighted how the dual stigma that PWID of Indigenous ancestry face when trying to access healthcare can result in delaying or forgoing needed care altogether . Collectively, these findings underscore the need for safe and culturally‐appropriate health services to optimize engagement in HCV care and improve health outcomes among Indigenous people.…”
Section: Discussionmentioning
confidence: 99%
“…No study compared harms systematically using comparison groups associated with different screening approaches. Harms informed by the alladult review included physical harms of screening (two studies) (48,49); anxiety/stress related to testing or waiting for results (five studies) (49-53); cost (one study) (54); anxiety related to receiving positive results (one study) (55); interpersonal outcomes (e.g., problems related to family, friends from learning HCV infection status) (five studies) (51,(55)(56)(57)(58); attitudes toward persons with hepatitis C, including stigma (11 studies) (49,55,(57)(58)(59)(60)(61)(62)(63)(64)(65); time for screening (two studies) (49,66); and false-positive results, including among left ventricular assist device patients, possibly precluding heart transplantation (six studies) (67)(68)(69)(70)(71)(72). Harms informed by the pregnancy review included physical harms of screening (one study) (73), anxiety (five studies) (74)(75)(76)(77)(78), stigma (one study) (77), psychological issues (two studies) (73,79), fears related to sexual relationships (one study) (80), legal ramifications and potential loss of infant custody (one study) (81), decreased quality of life (one study) (82), social repercussions (one study)…”
Section: Summary Of the Literaturementioning
confidence: 99%
“…Studies of patients with liver disease worldwide have suggested that patients' explanations of symptoms (such as fatigue and tiredness) may be influenced by folk health beliefs, which affect the health behaviours and management of the disease, including adopting new lifestyles or alternative/traditional treatments (Brener et al, 2016 (Fang & Stewart, 2018), remedial or healing herbs (Fang & Stewart, 2018;Giles-Vernick et al, 2016). In the patients' experience, these treatments are often used as alternative treatments instead of usual medical treatment (Fang & Stewart, 2018;Lee et al, 2017;Owiti et al, 2015).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Studies of patients with liver disease worldwide have suggested that patients’ explanations of symptoms (such as fatigue and tiredness) may be influenced by folk health beliefs, which affect the health behaviours and management of the disease, including adopting new lifestyles or alternative/traditional treatments (Brener et al, ; Burnham et al, ; Owiti, Greenhalgh, Sweeney, Foster, & Bhui, ). Traditional treatments are often related to cultural beliefs, including spiritual healing (Fang & Stewart, ), remedial or healing herbs (Fang & Stewart, ; Giles‐Vernick et al, ).…”
Section: Introductionmentioning
confidence: 99%